Implementasi Framework Laravel Dalam Pembuatan Sistem Pencatatan Notula Berbasis Website - Ahmad Azhar Kadim; Lillyan Hadjaratie; Muthia Muthia (Diponegoro University, 2023)
Minutes of Meeting are notes that function to record the things discussed in a meeting agenda. Minutes of Meeting are important and must exist so that agreements and decisions can be saved, so that they can be discussed again on the agenda of the next meeting. With the development of current technology, it is hoped that it can be implemented in various ways, one of which is that Minutes which were previously only written in books can be presented on the website so that it can facilitate monitoring and evaluation quickly, precisely, anywhere, and anytime. This study aims to realize a Web-based E-Notulen system by utilizing the Laravel framework and the Waterfall method for design which includes Analysis, Data Requirements, Design, Development, Testing, and Implementation. Based on the method used, the E-Notulen system can be designed by utilizing the existing Laravel Framework library using the Waterfal method. The Waterfall method can be applied in system development, especially systems that require fast time from design to implementation such as the E-Minutes system.